Belowground biotic complexity drives aboveground dynamics: a test of the soil community feedback model. Issue 4 (11th January 2013) - Pendergast, Thomas H.; Burke, David J.; Carson, Walter P.
Summary: Feedbacks between soil communities and plants may determine abundance and diversity in plant communities by influencing fitness and competitive outcomes. We tested the core hypotheses of soil community feedback theory: plant species culture distinct soil communities that alter plant performance and the outcome of interspecific competition. We applied this framework to inform the repeated dominance of Solidago canadensis in old‐field communities. In glasshouse experiments, we examined the effects of soil communities on four plant species' performance in monoculture and outcomes of interspecific competition. We used terminal restriction fragment length polymorphism (TRFLP) analysis to infer differences in the soil communities associated with these plant species. Soil community origin had strong effects on plant performance, changed the intensity of interspecific competition and even reversed whether plant species were limited by conspecifics or heterospecifics. These plant–soil feedbacks are strong enough to upend winners and losers in classic competition models. Plant species cultured significantly different mycorrhizal fungal and bacterial soil communities, indicating that these feedbacks are likely microbiotic in nature. In old‐fields and other plant communities, these soil feedbacks appear common, fundamentally alter the intensity and nature of plant competition and potentially maintain diversity while facilitating the dominance of So. canadensis .